Fiscal-monetary policy mix: Challenges facing the EU - Ernest Gnan; Robert Holzmann (Oesterreichische Nationalbank (OeNB), 2025)
Starting from the Tinbergen principle and four areas of economic policy, we argue that in practice economic policies each have multiple effects, rendering a clear and simple allocation of objectives and instruments to different policies and their responsible institutions complex. First, the case of demand and supply shocks is briefly outlined. Then, after a summary of the discussion on the policy mix since the 1960s, the concepts of monetary versus fiscal dominance are juxtaposed, while noting the existence of intermediate regimes. Finally, key features of the fiscal-monetary-structural policy institutional setup in the euro area are presented. The paper concludes with design shortcomings of this setup, the forces driving its incremental evolution over time, and future challenges.
Keywords: 330; fiscal-monetary policy mix; policy coordination; fiscal dominance; monetary dominance; fiscal backing; quantitative easing; European economic governance; EMU; European integration